Analisis Perbandingan Biaya dan Waktu Metode Pelat Konvensional (Cast In Situ) dengan Metode Half Slab Precast pada Proyek Pembangunan RS UPT Vertikal Surabaya - Gunawan, Rachmat; Dita Pahang Putra, I Nyoman; Puspitasari, Nia Dwi (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2024)
The construction project of UPT Vertical Hospital is located in Surabaya, East Java. The project uses a conventional method for its floor slab structure, but the method has many drawbacks such as requiring a lot of labor for formwork work, being highly dependent on weather conditions, and not guaranteeing the quality of concrete in the connection area. For this reason, the precast half slab method will be planned as an alternative solution. This research aims to determine the results of comparative analysis between the conventional method (cast in place) and the half slab precast method in terms of cost and time. The method used in this research is a comparative quantitative method. The results of the analysis of the two methods are the conventional method takes 160 days and costs Rp. 13,315,000,000.00 while the half slab precast method takes 140 days and costs Rp. 10,736,000,000.00. In conclusion, the more efficient method used is the half slab precast method because the method takes 20 days less time and the difference in cost is Rp. 2,579,000,000.00 cheaper than the conventional method (cast in place).